2004
DOI: 10.1128/jcm.42.3.1243-1246.2004
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Presence of Decorin-Binding Protein B (BBA25) and BBA50 Antibodies in Cerebrospinal Fluid of Patients with Neurologic Lyme Disease

Abstract: Borrelia burgdorferi antibodies preferentially present in cerebrospinal fluid (CSF) were examined by differentially probing a B. burgdorferi expression library with CSF and sera from patients with neurologic Lyme disease. Several phage clones selectively reacted with CSF, and these genes were then expressed in recombinant form and used to detect specific antibody in an enzyme-linked immunosorbent assay. Decorin-binding protein B (BBA25) and BBA50 (hypothetical protein) elicited immunoglobulin G (IgG) or IgM de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…These enzymes linked by an activation cascade may lead to the focal and transient degradation of tight junction proteins that allows B. burgdorferi to invade the CNS, yet our preliminary experiments indicated that B. burgdorferi cells could bind via their tips prior to crossing the in vitro human BBB model (data not shown) and that they did so without evidence of breakdown of the BBB integrity based on endpoint Endohm TEER measurements. The TEER and permeability data are consistent with what has been observed in vivo; i.e., unlike what is seen in purulent bacterial meningitis, B. burgdorferi infection usually causes aseptic meningitis in which the permeability of the BBB is not substantially altered (18).…”
Section: Discussionsupporting
confidence: 76%
“…These enzymes linked by an activation cascade may lead to the focal and transient degradation of tight junction proteins that allows B. burgdorferi to invade the CNS, yet our preliminary experiments indicated that B. burgdorferi cells could bind via their tips prior to crossing the in vitro human BBB model (data not shown) and that they did so without evidence of breakdown of the BBB integrity based on endpoint Endohm TEER measurements. The TEER and permeability data are consistent with what has been observed in vivo; i.e., unlike what is seen in purulent bacterial meningitis, B. burgdorferi infection usually causes aseptic meningitis in which the permeability of the BBB is not substantially altered (18).…”
Section: Discussionsupporting
confidence: 76%
“…This may be due to differences in technique or the arrayed stocks of these mutants may be contaminated with infectious mutants that masked the infectivity defect. Experimentally, antibodies recognizing BBA50 and BBA51 have been found in the cerebral spinal fluid and sera of patients with neurologic Lyme disease suggesting that they may be present on the bacterial surface at some point during vertebrate infection (Fikrig et al ., ). Together with bba48 , bba50 and bba51 may constitute an operon contributing to bacterial fitness during infection.…”
Section: Resultsmentioning
confidence: 97%
“…B. burgdorferi bacteria within the midguts of unfed ticks are relatively somnolent and probably do not divide for months on end, whereas tick feeding induces rapid borrelial growth and division times on the order of 1 to 2 h per cycle (12,22,67,68,69,87). It is probably not a coincidence that several genes associated with mammalian infection are both positively influenced by EbfC and upregulated during transmission (26,27,34,35,36,38,39,48,60,66,79,80). Conversely, the current studies found that EbfC repressed transcription of oms28/ORF BBA74, a gene that is expressed during tick colonization but not during vertebrate infection (64).…”
Section: Discussionmentioning
confidence: 99%
“…The positively affected dbpB gene encodes decorin-binding protein B, an outer surface protein involved with adherence to host tissues during mammalian infection (26,27,28,37,38,79,80). B. burgdorferi encodes two proteins that show similarity to the E. coli xylose-responsive regulatory protein, XylR-1 and XylR-2 (32).…”
Section: Ebfc Is a Nucleoid-associated Proteinmentioning
confidence: 99%